Potensi Sektor Ekonomi Unggulan Kabupaten/Kota di Jawa Tengah dengan Metode Dynamic Location Quotient Versi Bank Dunia - Endang Setiasih (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2008)
Regional economic potencies in Central Java Province is an interesting object to examine. Many regencies in the province has relied on agriculture sector be a primary income source in 2000, but, the sector has showed decreasing contribution in 2004. Beside that, new city raising, since 1999, has also affected to the structural economy changing because it leaded modern economic activity to stimulate regional income increasingly. By Static Location Quotient (LQ), this research shows that some superior economic sectors has change in 2000 to 2004, among regencies and cities. The tendency of the changing has an implication of the growth of role in every sectors, relatively among the regions. By Dynamic Location Quotient (LQ), this research shows some regions have lower LQ than others and coincide decreasing LQ value. If this empirical condition occurs in important sectors, it will has negative effect to economic condition of society. On the other side, some regions have higher LQ and positive LQ growth. It makes the economic sectors have positive potency and needs to keep improving by policy maker. Keywords: Static and Dinamic Location Quotient, potencies, regional